Role of external magnetic fields in determining the thermodynamic properties of iron carbides in steel. (1st April 2019) - Hou, T.P.; Li, Z.H.; Wu, K.M.; Lin, H.F.; Li, Y.; Zhang, G.H.; Liu, W.M.
Abstract: The experimental results indicated that a 12 T magnetic field effectively promoted the precipitation of metastable χ -Fe5 C2 iron carbides in low temperature tempered steel. A straightforward approach was proposed to analyze the thermodynamic mechanisms of iron carbides considering the combined effects of self-magnetism and external-field-induced magnetism. Our calculations revealed that the self-magnetic structure characteristics originated from the trigonal prism, which was composed of a lattice of six iron atoms surrounding a carbon atom positioned in the center of the framework. The external-field-induced magnetic exchange coupling increased the long and short-range magnetic order, which was inherently connected with changes in the Curie temperature, thereby altering the peak of magnetic entropy and enthalpy. The external-field-induced magnetism determined magnetic Gibbs free energy change, and further influenced on the precipitation stability of the iron carbides, which agreed well with the experimental results. These findings effectively illuminate the key magnetism problem for the Tokamak of the well-known ITER project for fusion energy and other Fe-based alloys and compounds in extreme conditions. Graphical abstract: Image 1